Omega-3 supplementation changes the physical properties of leukocytes but not erythrocytes in healthy individuals: An exploratory trial - Schuchardt, Jan Philipp; Kräter, Martin; Schlögel, Maximilian; Guck, Jochen; van Oirschot-Hermans, Brigitte A.; Bos, Jennifer; van Wijk, Richard; Tintle, Nathan L.; Westra, Jason; Kerlikowsky, Felix; Hahn, Andreas; Harris, William S. (Prostaglandins Leukotrienes and Essential Fatty Acids, 2024)
n3-PUFA impact health in several ways, including cardiovascular protection and anti-inflammatory effects, but the underlying mechanisms are not fully understood. In this exploratory study involving 31 healthy subjects, we aimed to investigate the effects of 12 weeks of fish-oil supplementation (1500 mg EPA+DHA/day) on the physical properties of multiple blood cell types. We used deformability cytometry (DC) for all cell types and Laser-assisted Optical Rotational Red Cell Analysis (Lorrca) to assess red blood cell (RBC) deformability. We also investigated the correlation between changes in the physical properties of blood cells and changes in the Omega-3 Index (O3I), defined as the relative content of EPA+DHA in RBCs. Following supplementation, the mean±SD O3I increased from 5.3 %±1.5 % to 8.3 %±1.4 % (p < 0.001). No significant changes in RBC properties were found by both techniques. However, by DC we observed a consistent pattern of physical changes in lymphocytes, neutrophils and monocytes. Among these were significant increases in metrics correlated with the cells’ deformability resulting in less stiff cells. The results suggest that leukocytes become softer and have an increased ability to deform under induced short-term physical stress such as hydrodynamic force in the circulation. These changes could impact immune function since softer leukocytes can potentially circulate more easily and could facilitate a more rapid response to systemic inflammation or infection. In conclusion, fish-oil supplementation modulates some physical properties of leukocyte-subfractions, potentially enhancing their biological function. Further studies are warranted to explore the impact of n3-PUFA on blood cell biology, particularly in disease states associated with leukocyte dysregulation.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Blood cell stiffness; Cell deformability cytometry; Lymphocytes; Monocytes; Neutrophils; Omega-3 index